2013
DOI: 10.1007/s40265-013-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Lorcaserin: A Review of its Use in Chronic Weight Management

Abstract: Oral lorcaserin (BELVIQ(®)), a selective serotonin 5-HT2C receptor agonist, is indicated in the US as an adjunct to diet and exercise in the chronic weight management of obese adults, or overweight adults with at least one weight-related comorbidity (e.g. dyslipidaemia, hypertension, type 2 diabetes). This article reviews the pharmacological properties, therapeutic efficacy and tolerability of oral lorcaserin in this patient population. In three large randomized, double-blind, multicentre studies, oral lorcase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The BLOOM-DM study (behavioural modification and lorcaserin for obesity and overweight management in diabetes mellitus), which was a one-year clinical trial study, reported that lorcaserin was an effective drug for obesity and is associated with better glycaemic control in diabetic patients [54] . The main adverse effect of lorcaserin as reported by the 3 clinical trials was headache, while the risk of valvulopathy was comparable to that of the placebo [55] .…”
Section: Anti-obesity Drugs and Monoaminesmentioning
confidence: 94%
“…The BLOOM-DM study (behavioural modification and lorcaserin for obesity and overweight management in diabetes mellitus), which was a one-year clinical trial study, reported that lorcaserin was an effective drug for obesity and is associated with better glycaemic control in diabetic patients [54] . The main adverse effect of lorcaserin as reported by the 3 clinical trials was headache, while the risk of valvulopathy was comparable to that of the placebo [55] .…”
Section: Anti-obesity Drugs and Monoaminesmentioning
confidence: 94%
“…Serotonin (5-HT) is directly involved in the regulation of eating behavior [109] and reductions in 5-HT function have been associated with negative mood, an increased urge for binge eating [110], and increased consumption of high-fat sweet foods [111,112]. Conversely, increasing 5-HT through pharmacological intervention has been used for obesity treatment [113], but this SSRI intervention has been associated with increased risk of depression, suicide, and cardiac complication. In addition to 5HT in the brain and peripheral nervous system affecting mood and feeding behavior, the majority of 5HT circulates in the blood, often termed "peripheral 5HT".…”
Section: Perinatal Ssris Altered Metabolism and Motor Developmentmentioning
confidence: 99%
“…The approval has been based on a clinical study programme with lorcaserin that includes studies with a duration of 2 years. A comprehensive overview of this agent, including its clinical profile regarding efficacy and safety is given in the article by Hoy in this issue [17].The efficacy and safety of lorcaserin was investigated in large clinical trials , BLOSSOM [13] and BLOOM [18]), using doses of 10 mg lorcaserin twice daily in a randomized, multicentre, placebo-controlled, double-blind fashion. Significantly more patients receiving lorcaserin achieved a bodyweight reduction from baseline of C5 % and C10 % compared with the placebo group after 12 months.…”
mentioning
confidence: 99%
“…The approval has been based on a clinical study programme with lorcaserin that includes studies with a duration of 2 years. A comprehensive overview of this agent, including its clinical profile regarding efficacy and safety is given in the article by Hoy in this issue [17].…”
mentioning
confidence: 99%